Systematic Literature Review: Importance of Knowledge Sharing on Organization (Antecedents and Consequences) - Rochmaningsih, Ayuninda; Sridadi, Ahmad Rizki; Agustina, Tri Siwi (JURNAL AKUNTANSI DAN MANAJEMEN, 2024)
Sharing knowledge (Knowledge Sharing) is considered important to encourage employee behavior to improve employee performance and influence the results that leaders want for their members, for this reason the author concentrates on finding answers to what factors influence a person's decision to share their knowledge with colleagues. This research examines theories related to knowledge sharing behavior, by concluding 37 journals that discuss knowledge sharing. The author concludes that there are many factors that influence knowledge sharing behavior. The research started by searching for data on journal banks such as Scopusm, Emerald, ScienceDirect, Google Scholar, and other supporting websites, after that the author studied and grouped the antecedents of this knowledge sharing behavior, and concluded that knowledge sharing behavior was discussed in 5 different journals as an antecedent of knowledge behavior. This sharing and behavior is influenced by several factors such as organizational commitment (OC), ethical leadership (EL). Transformational Leadership, and Trust, as well as knowledge sharing research have been widely researched in various organizational sectors, especially profit organizations.